NEW WAY OF CONTROLLING Oryctes monoceros (COLEOPTERA, DYNASTIDAE), A COCONUT PEST IN GHANA - René Philippe; S.K. Dery (CORD, 2004)
Oryctes monoceros is one of the most dangerous pests in young coconut and oil palm plantings throughout West Africa.